2022
DOI: 10.22437/jkmj.v6i1.16514
|View full text |Cite
|
Sign up to set email alerts
|

Faktor yang Berhubungan dengan Pemberian Imunisasi Dasar pada Bayi di Wilayah Kerja Puskesmas PAAL X Kota Jambi

Abstract: Imunisasi adalah suatu cara untuk meningkatkan kekebalan tubuh seseorang secara aktif terhadap suatu penyakit, sehingga bila kelak terpapar dengan penyakit tersebut tidak akan menderita penyakit tersebut. Tujuan Penelitian ini adalah untuk mengetahui hubungan pengetahuan, dukungan keluarga dan peran petugas kesehatan terhadap pemberian imunisasi dasar pada bayi di wilayah kerja Puskesmas Paal X Kota Jambi. Penelitian ini merupakan penelitian kuantitatif dengan desain penelitian adalah Cross Sectional. Pada pen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
6

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 0 publications
1
3
0
6
Order By: Relevance
“…This research is in line with the analysis of Sari (2018) The results show a relationship between family support and immunization against measles in infants, p-value = 0.000; this means that mothers who receive support from their husbands in administering immunizations are compared to mothers who do not receive support from their husbands.…”
Section: Babies At the Sadabuan Health Centersupporting
confidence: 86%
“…This research is in line with the analysis of Sari (2018) The results show a relationship between family support and immunization against measles in infants, p-value = 0.000; this means that mothers who receive support from their husbands in administering immunizations are compared to mothers who do not receive support from their husbands.…”
Section: Babies At the Sadabuan Health Centersupporting
confidence: 86%
“…On the one hand, several studies have a dominant positive attitude from the respondents. Astuti 20 found that mothers' attitudes towards primary immunization previous studies 14 , which showed that most of the respondents had good knowledge of the study's results, namely 45 respondents (46.4%). Subsequent studies obtained the results that 19 respondents (48.72%) had good knowledge of immunization.…”
Section: Original Articlementioning
confidence: 96%
“…Hubungan dukungan keluarga dengan kelengkapan imunisasi dasar pada bayi usia 0-12 bulan. Dengan kata lain, memungkinkan ibu yang tidak mendapatkan dukungan keluarga akan cenderung tidak membawa bayinya untuk imunisasi karena didasari dengan tidak adanya dukungan dari keluarga ( Sari, Sayuti, & Andri, 2022).…”
Section: Pembahasanunclassified